Comparison of efficacy of intralesional 5-fluorouracil alone, intralesional triamcinolone acetonide alone and intralesional triamcinolone acetonide with 5-fluorouracil in management of keloids - Manzoor, Hina; Tahir, Kehkshan; Nasir, Asma; Mufti, Shaiqa; Shehzad, Atif (Journal of Pakistan Association of Dermatologists, 2020)
Objective To evaluate the efficacy of intralesional 5-fluorouracil alone, intralesional triamcinolone acetonide alone and combination of intralesional triamcinolone acetonide and 5-fluorouracil in treatment of keloids. Â Methods Ninety patients who fulfilled the inclusion and exclusion criteria were enrolled. Patients were randomly divided into three groups of 30 each. In group A; Intralesional 5-fluorouracil (5 FU) 50 mg/ml alone was used. In group B; Intralesional triamcinolone acetonide (TAC) 40mg/dl alone was used. In group c; combination of intralesional triamcinolone acetonide 40mg/dl (0.1ml) and 5-fluorouracil 50mg/ml (0.9ml) was used, on monthly basis for 6 months. Patients were assessed for efficacy, after 6 months of the treatment. Â Results Â Efficacy was achieved in 70 cases in which 22 were from 5 FU group, 21 were from TAC group, and 27 were from 5 FU + TAC group. Statistically significant difference was found between TAC Vs 5 FU+TAC group i.e. p-value=0.02 and between 5 FU Vs 5 FU+TAC group i.e. p-value=0.04. Â Conclusion The combination of 5-FU+TAC has better efficacy as compared to 5-FU alone group & TAC alone group in the management of keloids. Â